Factors Influencing Participation in Free Health Checkups Among Students at State High School 5 in Bengkulu City - Arita Hasoloan Simarmata; Fiya Diniarti; Berlian Kando Sianipar; Tuti Rohani; Hartian Pansori (Journal Hygeia Public Health, 2026)
The Free Health Check-up (CKG) is a health screening program conducted by health workers directly at the target location, so students do not need to go to a community health center except for follow-up care, with a target of 52–53 million students (Ministry of Health, 2025). Data from the Bengkulu Provincial Health Office (September 2025) shows that CKG coverage for school-aged children is only 2.6%. This study aims to analyze the factors influencing CKG participation among students at SMA N 5 in Bengkulu City. The study employs a quantitative method with a cross-sectional design. A sample of 84 tenth-grade students was selected using systematic random sampling. Data analysis utilized the chi-square test (SPSS 22) followed by a binary logistic regression analysis. The results of the univariate analysis showed that of the 84 respondents, 48 (57.1%) had a good level of knowledge, 48 (57.1%) had a supportive attitude, 65 (77.4%) were female, 51 (60.7%) rated the role of teachers as good, 50 respondents (59.5%) rated the role of health workers as good, 52 respondents (61.9%) rated the implementation of the Free Health Check. The results of the bivariate analysis indicate a significant association between knowledge (p = 0.000), attitude (p = 0.009), gender (p = 0.022), the teacher’s role (p = 0.023), and the teacher’s role (p = 0.000) regarding the Free Health Check-up (CKG) among 10th-grade students at SMA N 5 in Bengkulu City. Multivariate Results: The role of health workers was the dominant factor associated with the implementation of the free health check-up program for 10th-grade students at SMA N 5 Kota Bengkulu, with the highest Exp(B) value of 16.337. It is hoped that SMA N 5 Kota Bengkulu can continue to increase support for the implementation of the Free Health Check-up (CKG) program by strengthening the role of teachers in health promotion and education activities for students.